Factors for improving and moderating a successful supply chain - Shi, Yu Wen; Chen, Ping-Kuo; Ye, Yong (Journal of Business Economics and Management, 2019)
The purpose of this study is to explore whether the ability to adjust and redistribute resources has a positive effect on improving a supply chain’s competitive capabilities. In addition, we also verify whether information transparency is an antecedent to improving the ability to adjust and redistribute resources. Finally, this study explores the moderating effects of investment cost controls and absolute dominance on the relationship between information transparency and the ability to adjust and redistribute resources. A partial least squares (PLS) analysis was the main method used in this study. The empirical data were obtained from the International Manufacturing Strategy Survey (IMSS). Regarding the research results, in addition to the relationships among information transparency, resource adjustment and redistribution ability, and supply chain competitive capabilities, our research results demonstrated that overemphasizing investment cost controls and absolute dominance will moderate the relationship between information transparency and resource adjustment and redistribution ability and further lead to weak competitive capabilities.